2014
DOI: 10.5847/wjem.j.issn.1920-8642.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild hypothermia on the ROS and expression of caspase-3 mRNA and LC3 of hippocampus nerve cells in rats after cardiopulmonary resuscitation

Abstract: BACKGROUND: Cardiac arrest (CA) is a common and serious event in emergency medicine. Despite recent improvements in resuscitation techniques, the survival rate of patients with CA is unchanged. The present study was undertaken to observe the effect of mild hypothermia (MH) on the reactive oxygen species (ROS) and the effect of neurological function and related mechanisms. METHODS:Sixty-five healthy male Sprague Dawley (SD) adult rats were randomly (random number) divided into 2 groups: blank control group (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…[37] There has been some evidence that temperature reduction might lessen the activation of these executioner caspases, [38][39][40] which is consistent with our results (Fig 5). Our data shows significantly reduced levels of both caspase 3 and 7 ( Fig 5) as long as TH is administered within the first 4 hours, leading to a clear benefit in maintaining high cell population viability.…”
Section: Discussionsupporting
confidence: 91%
“…[37] There has been some evidence that temperature reduction might lessen the activation of these executioner caspases, [38][39][40] which is consistent with our results (Fig 5). Our data shows significantly reduced levels of both caspase 3 and 7 ( Fig 5) as long as TH is administered within the first 4 hours, leading to a clear benefit in maintaining high cell population viability.…”
Section: Discussionsupporting
confidence: 91%
“…Autophagy is the primary mechanism by which cytosolic proteins and organelles are degraded (18). However, excessive autophagy activation in neurocytes damaged by I/R can lead to non-apoptotic cell death (19,20), which is called autoghagic programmed cell death. Beclin1 activates critical steps in autophagy, including the formation and maturation of autophagosomes (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It is related to both cell survival and cell death, and is cellular context‐dependent. Most recently, a plethora of evidence has indicated that autophagy is tightly associated with cancers, and that this has become a new therapeutic target in cancer treatment . Rapamycin‐induced autophagy in MCF‐7 breast cancer cells delayed the attendance of Rad51 and breast cancer 1 (BRCA1) in DSBs upon radiotherapy, leading to the accumulation of DSBs and cell death .…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a plethora of evidence has indicated that autophagy is tightly associated with cancers, and that this has become a new therapeutic target in cancer treatment. [10][11][12] Rapamycin-induced autophagy in MCF-7 breast cancer cells delayed the attendance of Rad51 and breast cancer 1 (BRCA1) in DSBs upon radiotherapy, leading to the accumulation of DSBs and cell death. 13 Similarly, the sensitivity of pancreatic carcinoma cell PC-2 to radiotherapy was significantly enhanced postrapamycin treatments, and the upregulation of autophagy mediator Beclin-1 sensitized lung cancer cells to irradiation.…”
Section: Introductionmentioning
confidence: 99%